ZOOGEOGRAPHIC CHARACTERISTICS OF THE NOCTUID MOTHS (LEPIDOPTERA, NOCTUIDAE) OF COASTAL AND ISLAND ECOSYSTEMS OF THE NORTH-WESTERN CASPIAN SEA - G. M. Abdurakhmanov; A. G. Abdurakhmanov; N. S. Kurbanova; N. M. Melikova; B. M. Kuramagomedov (Юг России: экология, развитие)
It is the first time as zoogeographical characteristics of owlet moths (Lepidoptera, Noctuidae) is given. Areal analyze of owlet moths of coastal and island ecosystems of the North-Western part of the Caspian Sea has shown they can be subdivided into 9 zoological groups and this indirectly points the ways of this fauna forming.